Joint processing and fast encoding algorithm for multi-view depth video - Peng, Zongju; Han, Huimin; Chen, Fen; Jiang, Gangyi; Yu, Mei (EURASIP journal on image and video processing, 2016)
The multi-view video plus depth format is the main representation of a three-dimensional (3D) scene. In the 3D extension of high-efficiency video coding (3D-HEVC), the main framework for depth video is similar to that of color video. However, because of the limitation of the mainstream capture technologies, depth video is inaccurate and inconsistent. In addition, the depth video coding method in the current 3D-HEVC software implementation is highly complex. In this paper, we introduce a joint processing and fast coding algorithm for depth video. The proposed algorithm utilizes the depth and color features to extract depth discontinuous regions, depth edge regions, and motion regions as masks for efficient processing and fast coding. The processing step includes spatial and temporal enhancement. The fast coding method mainly limits the traversal of the CU partition and mode decision. Experimental results demonstrate that the proposed algorithm reduces the coding time and the depth video coding bitrate; the proposed algorithm reduces overall coding time by 44.24 % and depth video coding time by 72.00 % on average. In addition, there is a 24.07 % depth video coding bitrate reduction with an average of 1.65 % Bjontegaard delta bitrate gains.